A model to compare convective and radiant heating systems for intermittent space heating. (1st April 2018) - Wang, Zhe; Luo, Maohui; Geng, Yang; Lin, Borong; Zhu, Yingxin
Graphical abstract: Highlights: A validated dynamic thermal model based on thermal-electrical analogy was built. Intermittent heating should not be utilized in extremely cold conditions. Convective system was more suitable than radiative system for intermittent heating. The ways to enhance the heating capacity of radiative systems have been explored. This research shed some light on the debate of heating in China's HSCW region. Abstract: In this paper, a dynamic heat transfer model based on thermal-electrical analogy has been built to compare convective and radiative heating systems for intermittent heating. An experiment has been set up to validate the model we built. The RMS Error was within 0.5 °C, confirming the accuracy of the model. The validated model was then applied to compare four typical space heating systems, namely all-air, radiator, in-slab floor heating, and lightweight floor heating systems. The concept of "ineffective heat" has been proposed to explain why the intermittent heating could reduce heating load. Two ideal characters of heating systems have been identified for intermittent heating, i.e. high heating capacity and low thermal mass, both of which are crucial to shorten the preheat time and to reduce the ineffective heat. The results indicate that convective heating systems were more comfortable (more rapidly raise the indoor temperature) and more energy efficient (lower heating load) for intermittent operation than radiative heating systems. The performance gap between radiative and convective heating systems would be enlarged in colder conditions. Among the four heating systems, convective heating system was the most suitable one for intermittent heating, and floor heating was the most unsuitable one. Though belonging to radiative heating systems, the radiator performs differently from floor heating for its potential to enhance heating capacity and relatively low thermal mass. Additionally, outdoor climate and building thermal insulation level also affect the choice of the most suitable heating system and heating mode. The findings of this research might shed some light on the debate of the choice of space heating systems in areas with similar climate conditions with China's Hot Summer Cold Winter region.